Fulminant enterovirus 71 infection: Case report - Makonkawkeyoon K. (2017)
A previously healthy 3-year-old boy presented with high-grade fever, dyspnoea, alteration of consciousness, tachycardia and shock. A few erythematous macules and papules were seen on his palms and soles. Echocardiogram showed poor left ventricular contraction. Cardiac enzymes and pro-B-type natriuretic peptide were elevated. Milrinone, low-dose dopamine and intravenous immunoglobulin were administered. The patient recovered after 5 days without cardiac or neurological sequelae. The serological results showed a four-fold rise of enterovirus 71. In children with severe EV71 infection, early recognition of cardiopulmonary involvement and aggressive treatment are crucial to successful management. © 2010 Maney.